Remote effects of kidney drug transporter OAT1 on gut microbiome composition and urate homeostasis - Vladimir S. Ermakov; Jeffry C. Granados; Sanjay K. Nigam (JCI Insight, 2023)
The organic anion transporter OAT1 (SLC22A6, originally identified as NKT) is a multispecific transporter responsible for the elimination by the kidney of small organic anions that derive from the gut microbiome. Many are uremic toxins associated with chronic kidney disease (CKD). OAT1 is among a group of “drug” transporters that act as hubs in a large homeostatic network regulating interorgan and interorganismal communication via small molecules. The Remote Sensing and Signaling Theory predicts that genetic deletion of such a key hub in the network results in compensatory interorganismal communication (e.g., host-gut microbe dynamics). Recent metabolomics data from Oat1-KO mice indicate that some of the most highly affected metabolites derive from bacterial tyrosine, tryptophan, purine, and fatty acid metabolism. Functional metagenomic analysis of fecal 16S amplicon and whole-genome sequencing revealed that loss of OAT1 was impressively associated with microbial pathways regulating production of urate, gut-derived p-cresol, tryptophan derivatives, and fatty acids. Certain changes, such as alterations in gut microbiome urate metabolism, appear compensatory. Thus, Oat1 in the kidney appears to mediate remote interorganismal communication by regulating the gut microbiome composition and metabolic capability. Since OAT1 function in the proximal tubule is substantially affected in CKD, our results may shed light on the associated alterations in gut-microbiome dynamics.